More caution or more lenient: deciphering the role of negative affect in recognition and inference - Lu Li; Hehe Lu; Ke Jiang; Huilin Qiu; Chunting Lin (Cognitive Processing, 2026)

Are we attending to climate change? A systematic review of the cognitive science literature - Joshua M. Carlson; Lin Fang; Mikenna Weiler; Abigail Dawson (Cognitive Processing, 2025)

How phonological and orthographic decoding complicates the simple view of reading in Chinese: examining mediation through listening comprehension - Jiexin Lin; Haomin Zhang (Cognitive Processing, 2025)

Relationship between self-reported sleep and cognitive function: a specification curve analysis - Jia-Jie Xu; Guo-Jun Lin; Fang Fang; Jing Yu (Cognitive Processing, 2023)

Visuospatial working memory and the construction of a spatial situation model in listening comprehension: An examination using a spatial tapping task - Yun Lin; Norio Matsumi (Cognitive Processing, 2022)
The present study investigated how visuospatial working memory (VSWM) is involved in the construction of a spatial situation model for spatial passages presented auditorily. A simple spatial tapping condition, a complex tapping condition as a target-tracking task, and a control condition, were used to analyze the role of VSWM. To understand how individuals who differ in verbal working memory (VWM) capacity (determined with a listening span test) process spatial text during dual-task performance, individual differences in VWM capacity were analyzed. In two experiments, the participants listened to a spatial text at the same time as performing a spatial concurrent task or no concurrent task. The results of the free recall test in Experiment 1 showed that there were no differences between the tapping conditions in the high VWM capacity group; the low VWM capacity group had a lower performance in both spatial tapping tasks compared to the control condition. The results of the map drawing test in Experiment 2 showed that complex spatial tapping impaired performance in comparison to simple spatial tapping and the control condition in the high VWM capacity group; in the low VWM capacity group, both spatial tapping tasks impaired recall performance. In addition, the participants with high VWM capacity demonstrated better performance. Overall, the results suggest that individuals with high VWM capacity have more resources to process verbal and spatial information than those with low VWM capacity, indicating that VWM capacity is related to the degree of the involvement of VSWM.

The relationship between action anticipation and emotion recognition in athletes of open skill sports - Yu-Ling Shih; Chia-Yen Lin (Cognitive Processing, 2016)

Subjective present: a window of temporal integration indexed by mismatch negativity - Lingyan Wang; Xiaoxiong Lin; Bin Zhou; Ernst Pöppel; Yan Bao (Cognitive Processing, 2015)

Electroencephalography when meditation advances: a case-based time-series analysis - Jui-Feng Tsai; Shaw-Hwa Jou; WenChun Cho; Chieh-Min Lin (Cognitive Processing, 2013)

Improving image annotation via useful representative feature selection - Wei-Chao Lin; Michael Oakes; John Tait; Chih-Fong Tsai (Cognitive Processing, 2009)